E-Health and Digital Transformation in Increasing Accessibility of Health Services - loso judijanto; Hendra Nusa Putra; Benny Novico Zani; Dadang Muhammad Hasyim; Muntasir Muntasir (Yayasan Adra Karima Hubbi, 2024)
In many countries, accessibility of healthcare remains a major challenge, especially in remote rural and urban areas. This research is relevant because of the push towards the application of technology in the healthcare sector to improve healthcare accessibility worldwide. The objectives of this study are to evaluate the role of e-Health in improving healthcare accessibility, explore the impact of digital transformation in improving the quality and coverage of healthcare services, and to draw conclusions about the implications of e-Health implementation and digital transformation in the context of improving healthcare accessibility. This research method uses a literature analysis approach to collect and analyze data from various sources of information related to e-Health and digital transformation in health services. The results of this study show that the implementation of e-Health and digital transformation has brought significant impact in improving the accessibility of health services, especially through the utilization of telemedicine, electronic medical records, and health applications. This has enabled easier access for individuals to obtain medical consultations and health information, especially for those living in remote areas. The conclusion of this study shows that e-Health and digital transformation have great potential in improving healthcare accessibility. By continuing to develop and integrate technology in the health sector, we can achieve the greater goal of providing more equitable and affordable healthcare to the global community. These steps can help reduce disparities in access to healthcare and improve people's overall quality of life.